ゴウニチ ナンキョク キョウドウ ケンキュウ ニ カンスル ワークショップ ノ ホウコク オヨビ ソノ カンレン セイカ - 川口, 創; カワグチ, ソウ; 本吉, 洋一; モトヨシ, ヨウイチ; 渡邉, 研太郎; ワタナベ, ケンタロウ; 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Kawaguchi, So; Motoyoshi, Yoichi; et al. (2014)
P(論文) 2008年6月豪日両首相による共同宣言の中で豪日の南極研究協力の重要性がうたわれたことを受け,2009 年9 月9?11 日および2012 年12 月1 日に国立極地研究所において第一回および第二回豪日南極研究合同ワークショップが開催された.一連のワークショップは南極研究における豪日共同研究を効果的に行うためのプランを議論することにより,将来の豪日双方の国内プロジェクト案に資することを目的とした. The 1st and 2nd Australia─Japan Joint Workshops on Antarctic Science(Sep. 9?11, 2009 and Dec. 1, 2012, respectively) were held at the National Institute of Polar Research (NIPR), Tokyo, Japan, after the importance of Australian and Japanese collaboration in Antarctic research was re-affirmed by the Prime Ministers of both countries in a June 2008 joint communique. The purposes of these workshops were to propose a plan to maximize the two countries' Antarctic research efforts and to produce agreed reports to form the basis of the development of future project proposals from each country. departmental bulletin paper